Liver disease and dyslipidemia as a manifestation of lysosomal acid lipase deficiency (LAL-D). Clinical and diagnostic aspects, and a new treatment. An update - Bay, Luisa (2017)
Lysosomal acid lipase deficiency (LAL-D) is still a little recognized genetic disease with significant morbidity and mortality in children and adults. This document provides guidance on when to suspect LAL-D and how to diagnose it. It is recommended to add lysosomal acid lipase deficiency to the list of differential diagnoses of sepsis, oncological diseases, storage diseases, persistent diarrhea, chronic malnutrition, and hemophagocytic lymphohistiocytosis. It should also be considered in young patients with dyslipidemia and atherosclerosis as well as diseases associated with fatty liver and/or hepatomegaly. LAL-D should be suspected in patients with hepatomegaly, hyperlipidemia and/or elevated transaminases found during routine checks or testing for other conditions, and in patients with cryptogenic cirrhosis. At present, there is the option of a specific enzyme replacement treatment.